2020
DOI: 10.3390/ijms22010040
|View full text |Cite
|
Sign up to set email alerts
|

Wisteria floribunda Agglutinin-Positive Mac-2 Binding Protein as a Screening Tool for Significant Liver Fibrosis in Health Checkup

Abstract: Chronic liver disease is generally widespread, and a test for screening fibrotic subjects in a large population is needed. The ability of Wisteria floribunda agglutinin-positive mac-2 binding protein (WFA+-M2BP) to detect significant fibrosis was investigated in health checkup subjects in this research. Of 2021 health checkup subjects enrolled in this prospective cross-sectional study, those with WFA+-M2BP ≥ 1.0 were defined as high risk. Liver fibrosis was evaluated using magnetic resonance elastography (MRE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Advanced fibrosis was defined as FIB-4 ≥ 2.67, NFS ≥ 0.675, and WFA + -M2BP ≥ 1.0 cut-off index (COI), based on previous studies. [19][20][21][22][23][24][25] Cardiovascular disease risk assessment. Cardiovascular disease risk was assessed using Framingham risk score (FRS).…”
Section: Methodsmentioning
confidence: 99%
“…Advanced fibrosis was defined as FIB-4 ≥ 2.67, NFS ≥ 0.675, and WFA + -M2BP ≥ 1.0 cut-off index (COI), based on previous studies. [19][20][21][22][23][24][25] Cardiovascular disease risk assessment. Cardiovascular disease risk was assessed using Framingham risk score (FRS).…”
Section: Methodsmentioning
confidence: 99%
“…29 Therefore, although thresholds of FIB-4 vary by age, M2BPGi can measure liver fibrosis independent of age and may be useful for assessing liver fibrosis in the general population. 30 However, further validation studies are needed, especially in other regions outside Asia.…”
Section: Indirect Fibrosis Markersmentioning
confidence: 99%
“…Another study that compared M2BPGi and FIB‐4 demonstrated that optimal cutoff values of M2BPGi for advanced fibrosis were similar in age‐differ groups, while those of FIB‐4 increased in parallel with age 29 . Therefore, although thresholds of FIB‐4 vary by age, M2BPGi can measure liver fibrosis independent of age and may be useful for assessing liver fibrosis in the general population 30 . However, further validation studies are needed, especially in other regions outside Asia.…”
Section: Noninvasive Fibrosis Markers In Nafldmentioning
confidence: 99%
“…This marker is a useful predictor of NAFLD at fibrosis stages ≥ 2 and ≥ 3 [ 58 ], is not affected by age, and can be judged by a single cutoff point [ 59 ]. In addition, M2BPGi can differentiate patients at high risk for severe fibrosis from a healthy control group [ 60 ], and it may be a predictor of hepatocarcinogenesis, though further studies are required [ 61 ]. The M2BPGi clinical test is reimbursable in Japan, but limited data are available in other Asian-Pacific countries as highlighted in the 2016 Asian Pacific Association for the Study of the Liver consensus guidelines.…”
Section: Strengths and Weaknesses Of Each Nitmentioning
confidence: 99%